1998
DOI: 10.2307/2670105
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Inference on Network Traffic Using Link Count Data

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. American Statistical Association is collaborating with JSTOR to digitize, preserve and extend access to Journal of the American Statistical Association.We study Bayesian model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
240
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(242 citation statements)
references
References 3 publications
0
240
0
2
Order By: Relevance
“…Thus, if = { (i)} i∈I is consistent with A, then (i) is represented as in (4). As developed in West (1997), and then extended in Tebaldi and West (1998a) and Tebaldi and West (1998b), independent gamma priors on the multiplicative parameters in the log-linear model representation imply that all complete, univariate conditional posteriors are also of gamma form. Thus drawing new values for the model parameters, and hence the values of the (i), is immediately accessible using Gibbs sampling.…”
Section: Prior Specification and Posterior Sampling Of Model Parametersmentioning
confidence: 96%
“…Thus, if = { (i)} i∈I is consistent with A, then (i) is represented as in (4). As developed in West (1997), and then extended in Tebaldi and West (1998a) and Tebaldi and West (1998b), independent gamma priors on the multiplicative parameters in the log-linear model representation imply that all complete, univariate conditional posteriors are also of gamma form. Thus drawing new values for the model parameters, and hence the values of the (i), is immediately accessible using Gibbs sampling.…”
Section: Prior Specification and Posterior Sampling Of Model Parametersmentioning
confidence: 96%
“…Vardi (Vardi, 1996), Cao et al (Cao et al, 2000), and Tebaldi et al (Tebaldi & West, 1998) used the statistical inference method to estimate traffic matrix only over the local area network. As mentioned in (Soule et al, 2005), these methods are sensitive to the prior, and estimation errors are larger.…”
Section: Related Workmentioning
confidence: 99%
“…How to overcome the ill-posed nature in this problem is the main challenge faced. Network tomography is a good way for this problem (Cao et al, 2000;Tebaldi & West, 1998;Vardi, 1996;Zhang et al, 2003a).…”
Section: Problem Statementmentioning
confidence: 99%
“…Such an approach is also applied to the link delay inference problem under the same nonparametric model used in [3]. Some other related studies in traffic matrix estimation can be found in [8]- [11].…”
Section: B Previous Research and Our Contributionmentioning
confidence: 99%